2021
DOI: 10.1002/mc.23370
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐519d‐3p antagonizes osteosarcoma resistance against cisplatin by targeting PD‐L1

Abstract: Accumulating evidence indicates that a ligand of programmed cell death receptor‐1 (PD‐L1) participates in the progression and recurrence of multiple malignancies, including osteosarcoma. Nevertheless, the role of PD‐L1 in chemoresistance development is not fully understood. In the current study, we aim to clarify the interaction of miR‐519d‐3p and PD‐L1 in the development of cisplatin resistance. Immunohistochemistry, quantitative reverse‐transcription polymerase reaction, and Western blot were used to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…PD‐L1 also reportedly regulates cisplatin resistance in osteosarcoma. [ 23 ] Notably, intercellular PD‐L1 functions as an RNA binding protein to protect the mRNAs of NBS1 and BRCA1 from degradation and regulate DNA damage response, [ 11 ] possibly providing one explanation for how PD‐L1 leads to cisplatin resistance. Similarly, we have demonstrated that NPM PD‐L1 activates mTOR signaling to regulate osteosarcoma growth by binding with IGFBP3.…”
Section: Resultsmentioning
confidence: 99%
“…PD‐L1 also reportedly regulates cisplatin resistance in osteosarcoma. [ 23 ] Notably, intercellular PD‐L1 functions as an RNA binding protein to protect the mRNAs of NBS1 and BRCA1 from degradation and regulate DNA damage response, [ 11 ] possibly providing one explanation for how PD‐L1 leads to cisplatin resistance. Similarly, we have demonstrated that NPM PD‐L1 activates mTOR signaling to regulate osteosarcoma growth by binding with IGFBP3.…”
Section: Resultsmentioning
confidence: 99%
“…However, the downstream factor JUN interacts with the promoter of miR‐223 to upregulate its transcription, forming a miR‐223/Hsp70/JNK/JUN/miR‐223 feedback loop (Tang et al, 2018). A high level of miR‐340, miR‐340‐5p, miR‐138, miR‐203, miR‐519d‐3p, and miR‐217 shows drug sensitivity to DDP by stimulating cell death (Huang et al, 2021; Song, Duan, et al, 2017; Wang, Zhang, et al, 2022; Yan et al, 2018; Zhang, Guo, et al, 2015; Zhu et al, 2016). miRNAs can promote drug sensitivity by turning on the PI3K/AKT signaling pathway, which is a crucial strategy for overcoming chemotherapy resistance.…”
Section: Mirnas Associated With Drug Resistance In Osmentioning
confidence: 99%
“…Membrane-localized PD-L1 can combine with the PD-1 ligand on the T cell surface to inhibit immune cell proliferation and activity, thus helping tumor cells avoid immune monitoring. , Unlike that of the PD-L1 protein on the membrane, the role of PD-L1 in the cytoplasm is often neglected. In fact, recent research has shown that intracellular PD-L1 could promote tumor growth via a non-immune pathway. , Lou et al found that intracellular PD-L1 can act as an RNA-binding protein to regulate the mRNA stability of DNA damage repair (DDR) . In addition, high expression of PD-L1 can promote cisplatin or radiotherapy resistance. , …”
Section: Introductionmentioning
confidence: 99%
“…In fact, recent research has shown that intracellular PD-L1 could promote tumor growth via a non-immune pathway. 35,36 Lou et al found that intracellular PD-L1 can act as an RNA-binding protein to regulate the mRNA stability of DNA damage repair (DDR). 37 In addition, high expression of PD-L1 can promote cisplatin or radiotherapy resistance.…”
Section: ■ Introductionmentioning
confidence: 99%